2003
DOI: 10.1080/00050060310001707087
|View full text |Cite
|
Sign up to set email alerts
|

Unique aspects of stress in human service work

Abstract: Two unique stressors associated with human service work are emotional dissonance, particularly the need to hide negative emotions (emotion work), and client/customer‐related social stressors. The latter may involve disproportionate or ambiguous client/customer expectations and/or verbally aggressive customers. These stressors affect all human service workers, even though they may vary in the extent to which their work involves lasting relationships with clients/customers, and in the amount of training they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 46 publications
2
84
0
4
Order By: Relevance
“…For example health professionals typically develop long-lasting relationships with their clients, whereas call centre workers may have only a single brief interaction. In accordance with contemporary theories of work stress (conservation of resources, effort -reward imbalance, demand -controlsupport), Dollard, Dormann, Boyd, Winefield, and Winefield (2003) argue that social support and training designed to develop ''role separation'' are crucial resources needed to help service workers cope with the unique emotion stressors of their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…For example health professionals typically develop long-lasting relationships with their clients, whereas call centre workers may have only a single brief interaction. In accordance with contemporary theories of work stress (conservation of resources, effort -reward imbalance, demand -controlsupport), Dollard, Dormann, Boyd, Winefield, and Winefield (2003) argue that social support and training designed to develop ''role separation'' are crucial resources needed to help service workers cope with the unique emotion stressors of their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…The problem with the job satisfaction argument is that although the literature does accept that it has something to do with good performance in the encounter it has not been able to specify how 'consciousness of being satisfied' actual impacts on the behaviour. Even when perceived as relieving job stress, job satisfaction is unable to say what the optimal coping strategy is and what level of satisfaction actually counts (Dollard et al, 2003). Job satisfaction is itself a variable phenomenon and subject to reinterpretation and the intervention of psychological states (Fisher, 2000).…”
Section: A Perspective From Social Psychologymentioning
confidence: 97%
“…Research conducted with several "human service" occupations has found that social support is a key resource for the successful management of emotional labour (Dollard et al 2003). Several studies provide evidence that employees who perceive higher levels of social support at work tend to report lower levels of strain in response to emotional labour (Zapf 2002).…”
mentioning
confidence: 98%